Análisis de residuos de plomo en repollo de Costa Rica - Mora Alfaro, Luis Enrique (1984)
Lead residues analysis in cabbage. Cabbage and soil samples from the main cabbage growing areas of Costa Rica were analyzed for lead residues. Lead residues result from the use of lead arseniate as an insecticide and fungicide; some farmers believe that it is also a compacting agent of the cabbage head and they apply it in spite of its use being prohibited. Residues in the range of 6.85 ppm to 0.06 ppm were found. Only one sample showed no lead residues. Concentrations levels in the crop soils ranged from 8.5 to 1.1 ppm.